Altis® Adjustable Single Incision Sling System for Treatment of Intrinsic Sphincteric Deficiency: A 3-Year Follow-up Observational Study. Issue 8 (12th August 2022) - Morciano, Andrea; Marzo, Giuseppe; Caliandro, Dario; Fachechi, Giorgio; Giaquinto, Alessia; Campagna, Giuseppe; Panico, Giovanni; Ercoli, Alfredo; Muzzupapa, Giuseppe; Cicinelli, Ettore; Scambia, Giovanni; Cervigni, Mauro
Abstract : Importance: This article is a long-term follow-up study on the Altis adjustable single incision sling (Coloplast Corp.) in patients with isolated intrinsic sphincteric deficiency (ISD). Objectives: The primary end-points were to evaluate the subjective and objective outcomes of the Altis for the treatment of ISD, with a 3-year follow-up. The secondary end-point was to evaluate the safety of this surgical procedure. Study Design: This is a retrospective single-arm study. A total of 123 consecutive patients with ISD were selected from our database among women who underwent an Altis implantation for ISD from March 2015 to June 2017, after unsuccessful previous conservative treatment. Of the 123 included patients, 16 were excluded, not meeting inclusion criteria. Cure rate was evaluated objectively, using a standardized cough stress test and urodynamics, and subjectively using the Patient Global Impression of Improvement. Complications were assessed intraoperatively, perioperatively, and postoperatively. Six, 12, and 36 months of follow-ups were analyzed for the study. Results: The 3-year objective cure rate was 86.9%, and the subjective cure rate was 81.5%. We observed no intraoperative complications. No women were obstructed. Ten patients reported postoperative complications, although most of them were Clavien-Dindo grade I and self-limited. Conclusions: Altis system could be considered an effective and safe alternative to traditional midurethral slings as treatment for women with ISD.